The influence of newborn early literacy intervention programs in three canadian provinces. (2nd October 2015) - Letourneau, Nicole; Whitty, Pam; Watson, Barry; Phillips, Jennifer; Joschko, Justin; Gillis, Doris
Abstract : Low levels of literacy in early childhood can have lasting effects on children's educational and intellectual development. Many countries have implemented newborn literacy programs designed to teach parents pre-literacy promoting activities to share with their children. We conducted 2 quasi-experimental studies using 1) a pre-test/post-test design and 2) a non-equivalent control group design to examine the effect of newborn literacy programs on parents' self-reported literacy intentions/behaviors, values toward literacy, and parent-child interactions. Parents were recruited from 3 provinces, 2 with newborn literacy programs (intervention) and 1 without (control). Parents in the intervention group completed prenatal and postnatal (after participation in program) questionnaires. Parents in the control group completed 1 questionnaire. Questionnaires were designed to capture parents' literacy intentions (prenatal), behaviors (postnatal), values, and parent-child interactions (postnatal). A total of 98 parents were included in study one and 174 were included in study two. Parents' self-reported prenatal intentions and values were higher than their postnatal behaviors and values. Parents in the intervention group exhibited higher literacy behaviors and values and greater enjoyment reading to their children than parents in the control group, though they also reported reading to their children less frequently. Parents in the intervention group had significantly higher Positive Interactive scores than controls. Overall, we found participation in newborn literacy programs positively impacted parenting behaviors and attitudes. Lower postnatal within-group scores (intentions and values versus behaviors and values) may have been the result of participants' high expectations. Given our findings, we recommend that these programs continue.